The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/1873-3468.13067
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of primary microRNA processing

Abstract: Edited by Wilhelm JustMicroRNAs (miRNAs) are evolutionarily conserved small regulatory RNAs that participate in the adjustment of many, if not all, fundamental biological processes. Molecular mechanisms involved in miRNA biogenesis and mode of action have been elucidated in the past two decades. Similar to many cellular pathways, miRNA processing and function can be globally or specifically regulated at several levels and by numerous proteins and RNAs. Given their role as fine-tuning molecules, it is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 127 publications
0
72
0
Order By: Relevance
“…Acting together, small RNAs and Ago proteins form the 'RNAinduced silencing complex' (RISC) (Hammond et al 2000) where the small RNA serves as specificity factor that direct bound effector protein to its target mRNAs via base-pairing interactions (Carthew & Sontheimer 2009). The~22 nucleotides long microRNAs are the dominating class of small RNAs and are found broadly throughout plant and animal kingdoms (Creugny et al 2018). Several studies have demonstrated the existence of microRNA biogenesis in penaeid shrimp, supporting that such pathway is an evolutionarily conserved mechanism of post-transcriptional gene regulation (Fig.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Acting together, small RNAs and Ago proteins form the 'RNAinduced silencing complex' (RISC) (Hammond et al 2000) where the small RNA serves as specificity factor that direct bound effector protein to its target mRNAs via base-pairing interactions (Carthew & Sontheimer 2009). The~22 nucleotides long microRNAs are the dominating class of small RNAs and are found broadly throughout plant and animal kingdoms (Creugny et al 2018). Several studies have demonstrated the existence of microRNA biogenesis in penaeid shrimp, supporting that such pathway is an evolutionarily conserved mechanism of post-transcriptional gene regulation (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…The ~22 nucleotides long microRNAs are the dominating class of small RNAs and are found broadly throughout plant and animal kingdoms (Creugny et al . ). Several studies have demonstrated the existence of microRNA biogenesis in penaeid shrimp, supporting that such pathway is an evolutionarily conserved mechanism of post‐transcriptional gene regulation (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Besides being induced by thermal and other cell stress conditions, Hsp83 is ubiquitously expressed during normal development. It is involved in a wide variety of cellular processes like protein chaperoning, chromatin modification through binding with DNA, formation of pre-RISC complex, piwiRNA biogenesis, sno/sn/telomerase RNA accumulation, cell cycle regulation, signaling pathways, transgenerational inheritance and molecular evolution (Bandura et al 2013; Basto et al 2007; Boulon et al 2010; Creugny et al 2018; Cutforth and Rubin 1994; DeFranco and Csermely 2000; Dittmar and Sen 2018; Gangaraju et al 2011; Graf and Enver 2009; Iwasaki et al 2015; Lange et al 2000; Mazaira et al 2016; Miyoshi et al 2010; Olivieri et al 2012; Pratt and Toft 1997; Ruden and Lu 2008; Rutherford et al 2007; Sawarkar et al 2012; Specchia et al 2010; Tariq et al 2009; van der Straten et al 1997; Zhao et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of hsrω transcripts affects intra-cellular dynamics of the diverse hnRNPs (Lakhotia et al 2012;Piccolo et al 2017; Piccolo and Yamaguchi 2017) while Hsp83/Hsp90 is known to bind (Sawarkar et al 2012; Singh and Lakhotia 2015; Tariq et al 2009) with promoters of several highly down-regulated genes in Sp/CyO; hsrω 66 Hsp90GFP larvae. Hsp90 and a variety of hnRNPs also directly interact and regulate a wide variety of cellular activities (Chen et al 2007; Chi et al 2018; Creugny et al 2018; Ford et al 2002; Grammatikakis et al 1999; Jinwal et al 2012; Lackie et al 2017; Youn et al 2018; Zhang et al 2006). Apparently, the altered dynamics of hnRNPs due to the near absence of hsrω transcripts in hsrω 66 in conjunction with elevated Hsp83 levels severely affects transcripts of many genes, including those like l(2)gl, kuz, mmp2, SPARC etc, to generate the unusual phenotype of the rare surviving Sp/CyO; hsrω 66 Hsp90GFP larvae.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in this Prague Special Issue we present a broad selection of Review articles contributed by invited speakers addressing topical questions. The areas covered include Plant Biology, focusing on the function of the kinesin‐14 family, host‐pathogen interactions, the use of the CRISPR‐Cas system in plant breeding and the mechanosensors MSL10 and DEK1 ; RNA Biology, including contributions on micro‐RNA processing, native nucleic acid structure, epitranscriptomic mRNA modification, telomerase reverse transcription and the locus‐specific mapping of 5‐methylcytosine and its oxidized derivatives ; Metabolism, with contributions on acetyl‐CoA carboxylase targeting, isoprene synthesis in Cyanobacteria and bile acid hydroxyl group oxidation and the gut microbiome ; Cellular Signaling, discussing the role of FOXO proteins in cellular senescence, temperature control of obesity, the role talins play in integrin signaling and nitric oxide synthesis by molybdenum enzymes ; Chemical Biology of Thiols, focusing on hydropersulfides and related polysulfides . In addition, there are contributions on structural data archiving , the iNEXT network presented by Banci , DNA‐encoded chemical libraries and DNA‐functionalized biomedical surfaces .…”
mentioning
confidence: 99%